(untitled) (Baghdad Science Journal, 2010)
The aqueous extract of banana fruits peal was tested for its effect on mitosis . The root tips of Allium cepa were used as plant test system and the bone marrow cells of the albino mice Mus musculus were used as mammalians test system in vivo .Root tips of Allium cepa were treated for four hours with five concentrations of the extract (5 , 10 , 20 , 40 ,60 mg / ml.).The Metaphase was arrested in all the treatments , the highest percentage ( 100 % ) was recorded in the first concentration , the last concentration caused stickiness and clumping of the chromosomes. The treatments did not cause significant difference in the mitotic index. The peals extract (5 mg /ml) was compared with the extracts of fruits bulb, leaves and roots of banana plant, it was found that the extract of fruits peal is the best considering the highest percentages of arrested Metaphase in the root tips cells. The albino mice Mus musculus were injected intraperitonial with the peals extract ( 0.01 , 0.02, 0.04, 0.06, 0.08 mg / gm body weight), the percentages of arrested Metaphase in the bone marrow of these animals were comparable to the recorded percentages when the animals were injected with colchicine ( 0.01 mg / gm b.w.) .This study revealed the antimitotic activity of the aqueous extract of banana fruits peal on both the plant and mammalian cells in vivo. Studies will be conducted to investigate the effect of the extract and its components on the proliferation of cancer cells in vitro and in vivo.